Translational Research in Veterinary Oncology: From Bench Discoveries to Clinical Applications for Enhanced Cancer Care in Animals - Anand Gudur (Revista Electronica de Veterinaria, 2024)
The field of veterinary oncology stands at a pivotal juncture, where translational research plays a crucial role in bridging the gap between bench discoveries and clinical applications. With cancer being a leading cause of morbidity and mortality in companion animals, the integration of cutting-edge scientific findings into clinical practice holds immense promise for advancing cancer care and improving outcomes. At the forefront of this endeavor lies a multidisciplinary approach that leverages insights from molecular biology, immunology, genetics, and pharmacology. Through a synergistic collaboration between basic scientists, clinicians, and veterinary oncologists, novel therapeutic strategies are being developed and refined, tailored to the unique biological characteristics of various tumor types encountered in veterinary patients. Key areas of focus in translational research include elucidating the molecular mechanisms underlying cancer initiation, progression, and metastasis, as well as identifying biomarkers for early detection, prognostication, and treatment response assessment. By unraveling the intricate interplay between tumor cells and the host microenvironment, researchers aim to devise targeted therapies that disrupt oncogenic signaling pathways while sparing normal tissues. Immunotherapy represents a paradigm shift in cancer treatment, with recent advances in veterinary oncology mirroring those in human medicine. From checkpoint inhibitors to chimeric antigen receptor (CAR) T-cell therapy, immunomodulatory approaches are revolutionizing the management of certain malignancies, offering new hope for patients previously deemed incurable.